2020
DOI: 10.1108/srj-10-2017-0199
|View full text |Cite
|
Sign up to set email alerts
|

University social responsibility: perceptions and advances

Abstract: Purpose The purpose of this paper is to analyze the perception of professors, students, administrative staff and academic directors about social responsibility in four universities of Rio Grande do Norte (RN) – Brazil. Design/methodology/approach The research was carried out in four universities in RN, Brazil. A survey was conducted with 1,318 students, 118 members of the administrative team, 104 professors and 29 academic directors, to whom a Likert-type questionnaire was applied, with 65 items allocated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 25 publications
0
23
0
4
Order By: Relevance
“…Based on the conviction that university business students should be familiar with the SR concept and apply it to their future professional projects, we questioned their perceptions of this concept. To date, studies have shown a generalized lack of knowledge about SR [10][11][12], which is why Lämsä et al [13] demanded more empirical research on this subject. For Alonso-Almeida et al [14] little progress has been made since then (referring to the previous work), and research on attitudes to SR within the field of education is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the conviction that university business students should be familiar with the SR concept and apply it to their future professional projects, we questioned their perceptions of this concept. To date, studies have shown a generalized lack of knowledge about SR [10][11][12], which is why Lämsä et al [13] demanded more empirical research on this subject. For Alonso-Almeida et al [14] little progress has been made since then (referring to the previous work), and research on attitudes to SR within the field of education is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%
“…Una institución se define por su misión (Drucker, 2012). Cuando la RSU se incorpora a la misión, visión y valores, se materializa en su plan estratégico (Dowsett, 2020;Filho et al, 2019;Larrán Jorge et al, 2015) y en la forma en el que se implementa, ejecuta y controla, asegurando canales de retroalimentación que permiten la mejora continua (de Sousa et al, 2020;Karwowska, 2019).…”
Section: Revisión De La Literaturaunclassified
“…La Responsabilidad Social Universitaria (RSU) se define como el compromiso que asume la universidad frente a sus grupos de interés (de Sousa et al, 2020;Ferrero-Ferrero et al, 2018) y que genera el cambio para lograr la transformación social (Păunescu et al, 2017), política (Chile & Black, 2015) y económica (Chan et al, 2021) que demanda la sociedad hacia un desarrollo humano más sostenible (Aleixo et al, 2018;Filho et al, 2019).…”
Section: Introductionunclassified
See 2 more Smart Citations